CLINICAL ASPECTS OF THERAPEUTICAL SOLUTIONS INVOLVED IN ORAL REHABILITATION OF PARTIALLY EDENTULOUS PATIENTS - Maria Bolat; Magda Antohe; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2014)
This study aims at identifying practical ways of approaching social cases, and creating a hierarchy of the final functions of restoration. In 2008 the Clinical Base for Learning from the Faculty of Dental Medicine, Iasi, recorded for the Partially Stretched Edentation Clinic and Therapy course a prevalence of biterminal partial edentation (Class I Kennedy)-66.39 per cent from the total number of patients, followed by uniterminal edentation (Class II Kennedy), having 40.24 per cent of the clinical cases, whereas INTERCALATE edentation (Class III Kennedy) , frontal edentation (Class IV Kennedy), and subtotal edentation have about 20.12.1 per cent each. The clinical form of edentation contributes to the election of a proper therapeutic solution as well as the odonto-parodontal and muco-osseous status of each clinical case, the patient's general condition or the socio economic and technical factors leading to a modern, classical or social prosthesing. An important aspect to be taken into account is the large percentage of 41.61.2/ social cases diagnosed with partially edentation, pleading for provisional prostheses with an established role in therapy, which sometimes may become social prosthesing - an outstanding clinical reality. Social cases should be solved with a view to restoring functionality such as lower level redimensioning and cranio-mandibulary repositioning, whereas aesthetic requirements fall into therapies based on metallo-ceramic and hybrid prosthesing or implanto-prosthetic therapy.